Revealing the Enhancement and Degradation Mechanisms Affecting the Performance of Carbonate Precipitation in EICP Process - Hu, Wenle; Cheng, Wen-Chieh; Wen, Shaojie; Yuan, Ke (Frontiers in Bioengineering and Biotechnology, 2021)
Given that acid-rich rainfall can cause serious damage to heritage buildings in NW China and subsequently accelerate their aging problem, countermeasure to protect their integrity and also to preserve the continuity of Chinese culture is in pressing need. Enzyme-induced calcite precipitation (EICP) that modifies mechanical properties of the soil through enhancing the inter-particle bonds by the precipitated crystals and the formation of other carbonate minerals is under a spotlight in recent years. EICP is considered as an alternative to the microbial-induced calcite precipitation (MICP) because cultivating soil microbes are considered to be challenging in field applications. This study conducts a series of test tube experiments to reproduce the ordinary EICP process, and the produced calcite precipitation is compared to that of the modified EICP process subjected to the effect of higher MgCl2, NH4Cl, and CaCl2 concentrations respectively. The modified EICP subjected to the effect of higher MgCl2 concentrations performs the best, with the highest calcite precipitation. The enhancement mechanism of calcite precipitation is well interpreted through elevating the activity of urease enzyme by introducing the magnesium ions. Further, the degradation of calcite precipitation presents when subjected to the effect of higher NH4Cl concentration. The decreasing activity of urease enzyme and the reverse EICP process play a leading role in degrading the calcite precipitation. Moreover, when subjected to the effect of higher CaCl2 concentrations, the slower rate of ureolytic hydrolysis and the decreasing activity of urease enzyme are primarily responsible for forming the ‘hijacking’ phenomenon of calcite precipitation. The findings of this study explore the potential use of the EICP technology for the protection of heritage buildings in NW China.